Dimming Techniques for Visible Light Communication System - Suriza A.Z.; Sharmin Akter; M. Shahnan (Institute of Advanced Engineering and Science, 2018)
Visible light communication (VLC) is an emerging and promising new technology in optical wireless communication (OWC). However, dimming has an adverse effect on the performance of visible light communication system. In visible light communication (VLC) system, illumination and communication both are provided simultaneously using a light emitting diode (LED). The specification for lighting is application specific for which dimming control is required. There are different modulation techniques for dimming control in visible light communication. In this thesis, NRZ-OOK modulation method and 4-QAM-OFDM modulation techniques are investigated for different dimming range, transmission distance, beam divergence angle and bit rate. The result shows that for 13m link range, 5Gb/s data speed is achievable for the 4-QAM-OFDM scheme. The analysis of this research is executed only based on system parameters. The scope of this research excluded the following parameters which are shadowing, mobility, multipath interference and inter-symbol interference for multicarrier modulation. These are the related research topic which can be investigated for future work.